(untitled) (Heritage, 2024)
As a part of religious revival in the 19th century church of the Saint Demetrius in the village Dobrotin near Lipljan, was renewed. In accordance with the donor’s inscription in the nave church was painted by Kostadin from Veles, with the help of his colleague Ignjat, in 1862. They created the decorative program of wall painting that was common for the parish churches in the Diocese of Raška and Prizren in the 19th century. It was based upon current iconographical recommendations and the wishes of the organizers who influenced the content. The program was organized in three horizontal zones on the walls, and vault was painted as well. Wall painting in the church of the Saint Demetrius bears different meanings, depending on the sacral topography of the church. While this program illustrates Christ’s incarnation and economy of salvation in the altar, in the nave active piety, that included righteous life, sacrifice for the religion and atonement of sin, is promoted. Simultaneously, program consists of saintly figures that had prominent role in the everyday life of the community, as healers and protectors. Also, national saints have prominent place in this program, as a part of national and religious glorification and identity creation.